COMMUNICATIVE TRADITIONS AND NEWS IN THE SCIENCE OF INFORMATIONAL SOCIETY - Броннікова, Л. (Proceedings of the National Aviation University Series Philosophy Cultural, 2018)
The article deals with changes in the system of communication in modern science. It is noted that fundamentally new forms of interaction between scientists do not arise. The transformation of traditional forms of cooperation of scientists is influenced by socio-cultural factors. One of the most important is the phenomenon of intellectual migration.